The association of renal cell carcinoma with gastrointestinal stromal tumors. Issue 8 (7th June 2018) - Mendonca, Shawn J.; Sanchez, Alejandro; Blum, Kyle A.; Ghanaat, Mazyar; Kashan, Mahyar Y.; Benfante, Nicole; Russo, Paul; Coleman, Jonathan A.; Crago, Aimee M.; Hakimi, A. Ari
Abstract : Background and Objectives: Prior small studies have reported a possible association between renal cell carcinoma (RCC) and gastrointestinal stromal tumors (GISTs). In the largest known series, our objective was to describe the prevalence of RCC among patients with GISTs over 26 years at Memorial Sloan Kettering Cancer Center (MSKCC). Methods: We retrospectively reviewed MSKCC's prospectively maintained sarcoma and RCC databases and identified all patients with both RCC and GIST between 1980 and 2016. Demographic and clinicopathological characteristics were obtained. Results: A total of 9/405 (2.2%) GIST patients were identified with RCC, with a mean follow‐up of 9.2 (range 3.8‐28.4) years. Five out of nine (55.6%) patients had RCC and GIST diagnosis within 6 months of each other. Mean RCC tumor size was 3.0 (range 1.8‐8) cm and 8/9 (88.9%) patients were RCC stage 1. A total of 4/9 (44.4%) patients had papillary RCC (pRCC) histology, 5/9 (55.6%) had additional alternative malignancies, and 4/9 (44.4%) had primary small bowel GIST. Conclusions: Our series suggests a possible association of RCC with GISTs. In addition, we found a high frequency of pRCC histology, alternative malignancies, and small bowel GISTs in co‐occurring RCC‐GIST patients. Further investigation to identify genetic mutations, in this population, would assist in surveillance and treatment.